Effect of irrigation protocols on root canal wall after post preparation: a micro-CT and microhardness study - Camila Maria Peres de Rosatto; Danilo Cassiano Ferraz; Lilian Vieira Oliveira; Priscilla Barbosa Ferreira Soares; Carlos José Soares; Mario Tanomaru Filho; Camilla Christian Gomes Moura (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: The aim of this study was to investigate the effects of different post space irrigation protocols for removing residual filling material from dentin walls, by using microcomputed tomography (micro-CT), and the influence of these protocols on dentin microhardness. Bovine incisors (n = 35) were filled with the single-cone technique and MTA Fillapex (Angelus, Londrina, PR, Brazil). Post space preparation (PSP) was performed 7 days after filling, using the Odous Touch electrical system (Odous De Deus Ind. e Com., Belo Horizonte, MG, Brazil), followed by post space irrigation using manual irrigation, passive ultrasonic irrigation, or Easy Clean, together with 2.5% sodium hypochlorite (NaOCl), or with 2.5% NaOCl and 17% EDTA (NaOCl/EDTA). Micro-CT scans were performed at three time points. The residual filling material was evaluated at three levels: cervical, middle and apical. The Knoop test was measured with four indentations around the canal lumen at three dentin depths: X (100 μm), Y (200 μm) and Z (400 μm). Statistical analysis was performed using ANOVA (p < 0.05). The effects of the activation method (p < 0.001), and the root level (p = 0.013), as well as the interaction between the irrigant and the activation method (p = 0.041), led to different percentages of residual filling material. Lower amounts of residual filling material were observed at the cervical versus the middle and apical levels (p < 0.05). No significant differences were observed in dentin microhardness (p > 0.05). The best removal of the residual filling material was performed using the Easy Clean tip and NaOCl/EDTA, regardless of the activation methods.